2020
DOI: 10.1109/access.2020.2970245
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach of Fuzzy Logic, AHP and TOPSIS for Estimating Usable-Security of Web Applications

Abstract: Security and usability are often thought of as being contradictive in nature. One affects the other negatively. The relation and trade-offs between usability and security must be detected during developing web application to satisfy the user's requirements with security perspective. Current approaches of usable-security emphasizes on building systems that are easy to use and secure as well. Hence, this paper is recognizing usability-security as a problem with different attributes contributing towards it. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 21 publications
0
81
0
1
Order By: Relevance
“…Furthermore, various university software applications were also used to verify the findings. Kumar et al [36] identified usability-security as a challenge with numerous attributes referring to it. In addition, they investigated that the question needs to be evaluated for the convenience of the end consumer.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, various university software applications were also used to verify the findings. Kumar et al [36] identified usability-security as a challenge with numerous attributes referring to it. In addition, they investigated that the question needs to be evaluated for the convenience of the end consumer.…”
Section: Related Workmentioning
confidence: 99%
“…Multiple approaches are available for solving the decision making problem. If multiple contentions occur at the time of calculation, then we can use MCDM approaches which support the experts' decision [18,19,20]. For medical device software security assessment, we have used the Fuzzy ANP-TOPSIS approach.…”
Section: Methodsmentioning
confidence: 99%
“…This paper covers the previous trends and attributes of malware attacks on the healthcare services and then tries to provide some significant factors with the help of experts' opinion that are affecting the healthcare organizations rapidly [16]. The article will also provide a scientific analysis of those factors through the hybrid approach of fuzzy AHP-TOPSIS methodology [17,18]. Fuzzy AHP-TOPSIS methodology is a pre-verified and old scientific multi criteria decision making technique that gives accurate as well as effective results in multi criteria decision situation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the first step of calculation, this paper used fuzzy AHP for evaluating the relevant weights through Equations (1)- (16). After that in next step, the experts prepared a comparison matrix and selected a variable with the help of Table 2 and Equation (18). In the following steps, the fuzzy matrix is normalized through Equation (19).…”
Section: Introductionmentioning
confidence: 99%